(untitled) - Darling, David J. (Hoboken, N.J., 2006)
This book recaps man's age-old quest to understand gravity, from Aristotle's ideas about objects falling to their "natural place" through Galileo, Newton, and Einstein. It explores some of the problems facing our current understanding of how gravity works, including the strange behavior of pendulums during eclipses and the anomalous trajectories of the deep-space Pioneer probes. And it considers possibilities for the future: efforts to detect gravity waves, the discovery of dark energy, and, in decades to come, devising a form of antigravity, achieving "warp drive," and even creating miniature black holes and embryonic universes.
Keywords: Gravitation,General relativity (Physics),Trọng lực,Thuyết tương đối; History,History,Lịch sử,Lịch sử